Investigating the Effect of Using Educational Podcasts on Listening Comprehension of Language Learners - Mohsen Fardavoodi; Morteza Bakhtiarvand; Salah Esmaeiligoujar. (Randwick International of Education and Linguistics Science Journal, 2020)
The aim of this study was to investigate the effect of using educational podcasts on listening comprehension of male language learners in Tehran. The statistical population of the present study consisted of all male language learners of Tehran language colleges who were studying in the academic year 2020-2019. The present study sample consisted of two target languages that were selected purposefully. There were 60 samples, of which 30 were in the control group and 30 in the experimental group. The type of research was quantitative and quasi-experimental with pre-test-post-test design with control group. To understand the required data, a researcher-made audit comprehension test was used. It was used to analyze the obtained data using SPSS software. The results showed that the use of educational podcasts is significantly more effective in increasing the listening comprehension skills of language learners of language schools F = 165/001 than the usual method. Based on the results, it is recommended to use educational podcasts in teaching audio-visual comprehension of learners, which is one of the main problems in language teaching.